2017
DOI: 10.1039/c6tb02312f
|View full text |Cite
|
Sign up to set email alerts
|

The effect of quercetin delivery system on osteogenesis and angiogenesis under osteoporotic conditions

Abstract: Bone regeneration under osteoporotic conditions with impaired angiogenesis, osteogenesis and remodeling represents a great challenge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 44 publications
1
51
0
Order By: Relevance
“…It was implanted into a bone defect created at the distal region of the femur diaphysis in ovariectomised rats. It was noted that the BMD and Tb.Th of the bone defects were improved after eight weeks of implantation [34].…”
Section: Type Of Animalmentioning
confidence: 91%
See 3 more Smart Citations
“…It was implanted into a bone defect created at the distal region of the femur diaphysis in ovariectomised rats. It was noted that the BMD and Tb.Th of the bone defects were improved after eight weeks of implantation [34].…”
Section: Type Of Animalmentioning
confidence: 91%
“…MSCs are adult stem cells capable of differentiating into osteoblasts, chondrocytes, myocytes, adipocytes, neurocytes and hepatocytes [100]. Using rat or mouse bone-marrow-derived MSCs, quercetin in various concentrations promoted proliferation, differentiation and mineralisation into osteoblastic lineage with a concomitant increase in the expression of ALP, osterix, Runx-2, COL1, BMP-2, BSP, osteopontin, osteocalcin, TGF-β1 and Cbfα1 [34,[62][63][64][65]. Adipose-derived stem cells are MSCs derived from adipose tissues.…”
Section: The Effects Of Quercetin On Osteoblastogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown that quercetin-functionalized hydroxyapatite can be useful for a local administration of the flavonoid since it enhances human OB-like cells proliferation and differentiation, whereas it downregulates osteoclasteogenesis 13 . Moreover, a recent study on in vitro and in vivo behavior of quercetin-loaded HA nanospheres, which has been performed on ovariectomized rat bone marrow derived mesenchymal stem cells and critical-sized femur defect model, indicates that the material could promote osteogenesis and angiogenesis, while inhibiting osteoclastogenesis, under osteoporotic conditions 14 . The results of a study on 3D porous calcium deficient hydroxyapatite scaffolds loaded with quercetin suggested that the beneficial influence of the flavonoid on bone tissue regeneration might be even greater than that of alendronate, one of the most potent bisphosphonates (BPs) 15 .…”
Section: Introductionmentioning
confidence: 99%